(3JQJjH eSfO GdTGaYis - (3CHh SYjO SfLQ Hf YHO Gddg GdfGUQi GdLGReis; (3GdGeGe GdTGaYj , CHh YHO Gddg,J (B204 (3g` s ((3eMeO Hf GHQGgje Hf YHjO Gddg s)
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQI HGH ai eGA GdHMQ s
(3BNQgG (B:s
(3jfJgi HHGH GdGNHGQ GdeJaQbI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG bQGAGJ YOjOIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs